Paradoxical cause of weaning failure: Post tracheostomy foreign body causing non‐resolving pneumonia with worsening failure to wean - Loveleen Mangla; Sagar Thote; Dhruv Talwar; Deepak Talwar (Respirology Case Reports, 2022)
Abstract The Percutaneous technique for tracheostomy has become the standard procedure, due to its ease in placement, minimal complications, and has almost replaced the traditional open (surgical) tracheostomy in intensive care units. We describe a case of broken tracheal cartilage which slipped into the tracheobronchial tree following percutaneous tracheostomy (PCT), impinging and causing collapse of medial basal segment of right lower lobe.